1979
DOI: 10.1128/aac.16.2.214
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Medium in Demonstrating Penicillin Tolerance by Group B Streptococci

Abstract: A total of 30 clinical isolates of group B streptococci were studied for penicillin tolerance in vitro. Minimal inhibitory and bactericidal concentrations of penicillin were determined simultaneously in three test media which have been used for group B streptococci, tryptose phosphate, Muelier-Hinton, and Todd-Hewitt broths, using a logarithmic-phase inoculum of 105 colony-forming units per ml.Minimal inhibitory concentrations in the three media did not differ significantly. However, minimal bactericidal conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…Clinically, lactobacillemia associated with deep-seated foci, particularly endocarditis, has been relatively refractory to high-dose parenteral therapy with the penicillins, despite MICs which are readily attainable in serum (1,13,19,20). Our previous studies have demonstrated that this discrepancy between in vitro activity and suboptimal therapeutic responses in vivo may be related to antibiotic tolerance of lactobacilli to f8-lactam and other antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, lactobacillemia associated with deep-seated foci, particularly endocarditis, has been relatively refractory to high-dose parenteral therapy with the penicillins, despite MICs which are readily attainable in serum (1,13,19,20). Our previous studies have demonstrated that this discrepancy between in vitro activity and suboptimal therapeutic responses in vivo may be related to antibiotic tolerance of lactobacilli to f8-lactam and other antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…ADPC MIC plate counts fell dramatically at the MIC and were essentially absent on plates with concentrations above the MIC as long as oxacillin action was permitted to continue. ADPC MBC plate-count patterns showed significantly less variation and inoculum phase (5,18,20,21,25,29), incubation time (1,19,22,26,34,36), and carry-over of antimicrobial agents from MIC tubes to MBC plates (12,19,31,33) have been shown to influence the measured incidence of tolerance and related phenomena for a variety of bacteria and antimicrobial agents. Less intuitively obvious has been the finding that bacteria subjected to broth dilution procedures may be inadvertently protected from the action of antimicrobial agents in broth cultures, thus causing tolerance interpretations to be spuriously high and often irregular in manifestation and reproducibility (15,26,39).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence has gradually accumulated indicating a significant dependency of BDPC results, especially MBCs, on technical factor variations. It is not surprising that factors such as pH (18,38), temperature (30), type of medium (22,28,32), VOL. 28, 1985 on clinical isolates and allegedly oxacillin-tolerant reference strains, Taylor and associates (36) compared results obtained by the standard broth macrodilution BDPC method as outlined in the Manual of Clinical Microbiology with those of a carefully controlled procedure patterned along the lines recommended by Ishida and associates.…”
Section: Methodsmentioning
confidence: 99%
“…It is clear from our studies and from those of others (1,3,5,6,8,12) that because there is a multiplicity of methodological determinants which affect the status of a given strain, a standardized reference procedure for the determination of tolerance needs to be established.…”
mentioning
confidence: 99%
“…Since then, tolerance has been described with a variety of other bacteria, including Staphylococcus aureus (1-4, 8, 9, 12-15), group D streptococci (7,10), and group B streptococci (6). Bacterial strains have been considered to be tolerant if they exhibit an MBC 8-to 100-fold greater than an MIC in the usual susceptible range (1,3,13,15).…”
mentioning
confidence: 99%